2022
DOI: 10.1097/md.0000000000030315
|View full text |Cite
|
Sign up to set email alerts
|

15-Year progression to liver cancer in the lack of treatment for lysosomal acid lipase deficiency: A case report

Abstract: Rationale: Lysosomal acid lipase deficiency (LAL-D) is a poorly diagnosed genetic disorder characterized by the accumulation of cholesteryl esters and triglycerides in many tissues, leading to dyslipidemia and cardiovascular complications. In the liver, deposits are found within hepatocytes and Kupffer cells, generating microvesicular steatosis, progressive fibrosis, and cirrhosis. Sebelipase alfa is the target therapy which can improve laboratory changes and reduce the progression of liver damage, but this is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…14 15 In humans, it has been reported that heterozygote carriers of LAL mutations altered subsets of human MDSCs, 16 and mutations in the LAL gene were linked to carcinogenesis. 17 Patients (ages ranging from 11 to 58 years) with LAL-D without enzyme replacement therapy of Sebelipase alfa (or Kanuma, commercial name for recombinant human LAL) developed hepatocellular carcinoma, cholangiocarcinoma, and hepatocellular cholangiocarcinoma, 18 suggesting that LAL serves as an attractive cancer therapy target. 19 Our recent study further supported the idea that human cancer xenotransplants were able to grow in Lal -/mice.…”
Section: What This Study Addsmentioning
confidence: 99%
“…14 15 In humans, it has been reported that heterozygote carriers of LAL mutations altered subsets of human MDSCs, 16 and mutations in the LAL gene were linked to carcinogenesis. 17 Patients (ages ranging from 11 to 58 years) with LAL-D without enzyme replacement therapy of Sebelipase alfa (or Kanuma, commercial name for recombinant human LAL) developed hepatocellular carcinoma, cholangiocarcinoma, and hepatocellular cholangiocarcinoma, 18 suggesting that LAL serves as an attractive cancer therapy target. 19 Our recent study further supported the idea that human cancer xenotransplants were able to grow in Lal -/mice.…”
Section: What This Study Addsmentioning
confidence: 99%